Influência da via de infecção na resposta imune de camundongos BALB/c infectados com a cepa ME-49 de Toxoplasma gondii - Queiroz, Guilherme Rosemberg Guimarães (1998)
The profile of the immune response was evaluated in the resistant immunocompetent BALB/c mice infected with Toxoplasma gondii by different inoculation routes. Female mice (6-8 weeks old) were orally or intraperitonealíy infected with 20 brain cysts of ME-49 strain of T. gondii. At different periods post-infection, i.e. 3, 12 and 21 days, blood samples were collected for immunoglobulin isotyping and their spleens and mesenteric and popíiteal lymph nodes were removed for measurement of the cytokine leveis in the supernatant of the cell suspensions submitted to cell culture. The survival rates were not different for the animais inoculated by the different routes. Serum samples of the animais infected with ME-49 strain presented antibodies that recognized antigens of the RH strain. The serological analysis showed that only the intraperitoneal infection induces the production of the detectable leveis of IgA and IgGl at day 12, even though the production of the IgG2a was detected for both routes of infection at this period. The spleen cells of the orally infected animais were able to produce IFN-y and IL-12 at day 3, 12 and 21 post-infection. In addition, the cells of this group were the only one that was able to produce IL-10. The orally infected mice also showed production of IL-12, when mesenteric and popíiteal lymph node cells were tested. It was not detected IFN-y in the culture of popíiteal lymph node cells, when the animais were infected by intraperitoneal route. Thus, these results suggested that the oral infection, the natural route of the host infection by T. gondii, should be included in the protocols which purpose is the study of the immunological features in experimental toxoplasmosis.